The Effect of the COVID‐19 Pandemic on South Korea's Stock Market and Exchange Rate. (2nd April 2021) - Hoshikawa, Takeshi; Yoshimi, Taiyo
Abstract : This study examines COVID‐19 pandemic effects on the stock market and exchange rate of South Korea. With daily data from January 2, 2019 to August 31, 2020, we show that a new infection spike increases stock price index volatility and decreases foreign investors' holdings of domestic stocks, and indirectly leads to the depreciation of the South Korean won. We indicate that investors may have repurchased the South Korean won seven days after an infection spike, thereby slightly increasing its value. We also find that the Bank of Korea's foreign exchange intervention had a short‐run effect with a limited impact. The intervention did not have a significant effect on exchange rate volatility.